Hate Speech Comments on Joe Biden™s Instagram Posts: Pragmatic Analysis - Aulia, Nindi; Lubis, Fauziah Khairani (TRANSFORM: Journal of English Language Teaching and Learning, 2022)
This study aimed to identifying the types of hate speech based on Mondal (2018) and the intentions of hate speech based on Kreidler (2002) in the comment section of Joe Biden™s Instagram posts. This study was conducted by applying descriptive qualitative method with thematic analysis. The source of the data is the hate comments from Joe Biden™s Instagram posts from 3rd November to 10th. The results of this research showed the classification of hate speech and the categorization of intentions of hate speech. From 150 data it was found there were 7 types out of 10 types of hate speech, they are 1 comment for type of Race, 57 comments for Behavior, 17 comments for Physical, 1 comment for Gender, 2 comments for Sexual Orientation, 6 comments for Disability and 66 comments for Other. However, for the intentions of hate speech, all comments contain all intentions that can be categorized. The intention that dominantly found is Insulting, Accusing, Mocking, Insinuating and Blaming.